INFLUENCE OF MULTIPLE TAKER-IN SYSTEM UPON TENSILE PARAMETERS OF COTTON YARN - Nawaz, Sheikh Muhammad; Shahbaz, Bahar; Khan, Nasrullah (Biological Sciences - PJSIR, 2002)
The study was aimed at comparing the effect of the conventional high production card with a modified card equipped with multiple taker-in system upon tensile parameters (viz., single yarn strength, elongation and ruph1re per kilometer) of 24' cotton yarn. The quality of yarn was significantly improved by the modified system. Thus by modifying and updating the webfeed system, an older carding machine can be made to produce yarn of impressive quality.